Pannaria byssoidea (Pannariaceae), a new squamulose species from Southern South America - Passo, Alfredo (2011)
The present contribution is part of an extensive revision of Pannariaceae in southern South America Nothofagus forests. Pannaria byssoidea is described as new to science from this area. The morphology, anatomy and chemistry of collections, including type specimens from Argentina, Chile and New Zealand were studied. The specimens from southern South America differ from those from New Zealand, and are here accommodated in a new species, P. byssoidea. The new species differs from P. implexa mainly in two characters: spore anatomy and medullary substance. The South American P. byssoidea is characterized by an orbicular squamulose thallus, surrounded by a thick byssoid prothallus, ellipsoid to subglobose ascospores, with roughened perispore, and the presence of leprolomin as medullary substance. Pannaria implexa is considered endemic to New Zealand, and is characterized by the ellipsoid ascospores, with a halonate perispore, and the presence of pannarin as medullary substance. Both species are illustrated and notes on their taxonomy, distribution and ecology are given.